Challenges Of Teaching English to Uzbek Pupils Of Secondary Schools Through Pragmatic Approach - Nigorakhon Bakhodirova (Pubmedia Jurnal Pendidikan Bahasa Inggris, 2025)
This study aims to identify the challenges in implementing a pragmatic approach in teaching productive English language skills to secondary school students in Uzbekistan. A qualitative research method was employed, including face-to-face interviews and structured observations. Twenty English teachers from the Namangan region participated in interviews discussing their awareness of the pragmatic approach, its advantages, and the challenges faced in its application. Additionally, observations were conducted over two months in 15 teaching sessions at various secondary schools. The findings indicate that the pragmatic approach effectively enhances students' communication, problem-solving, confidence, and collaboration skills. However, major challenges include time constraints, difficulties in assessment, and lack of student motivation. By integrating engaging activities and providing positive feedback, these challenges can be mitigated to improve the effectiveness of the pragmatic approach in English language teaching